Analisis Kemampuan Pemecahan Masalah Matematis Siswa Kelas VIII pada Materi Pola Bilangan - Novia Agustina; Dadang Rahman Munandar (Program Studi Pendidikan Matematika, Universitas Majalengka, 2022)
Mathematical problem solving is a skill that must be possessed by students because it is very important to solve problems and include goals in learning mathematics. But at the time of math learning some students have difficulty in solving problems because of the low mathematical problem-solving ability that students have. This research aims to describe the mathematical problem-solving ability of grade VIII students in solving mathematical problems in patterns of numbers. This research uses qualitative descriptive methods. Purposive sampling techniques were used to select subjects in the study, and selected 6 students as research subjects. This study uses 3 questions in the form of a description. The data collection techniques in this study are tests and interview skills. The study was conducted using the results of student answers analyzed based on indicators of problem-solving skills based on the Polya stage. The results of this study showed that students' mathematical problem-solving skills on indicators wrote information and wrote a settlement plan is 55.56% including moderate categories, then on the problem solving indicators is 44.45% including moderate categories, and on the indicator evaluate is 22.23% including low categories.